LINGUOCULTUROLOGICAL FEATURES OF PHRASEOLOGICAL UNITS IN THE WORKS OF N.V. GOGOL "THE GOVERNMENT INSPECTOR" AND KH.KH. NIYAZI "MAYSARA'S TRICKS" - Ibodullaeva Shirina Mirzhakhon Qizi (Western European Studies, 2024)
The article examines the linguoculturological features of phraseological units in the works of N.V. Gogol "The Government Inspector" and Kh.Kh. Niyazi "The Tricks of Maysara". The article examines how phraseological expressions in these works reflect cultural and social realities, elements of the worldview and identity of their authors and the societies in which they were created to understand the national culture and mentality. A comparative analysis of phraseological units allows us to identify both similarities and differences in the language system and cultural contexts of the two literary traditions, which contributes to a deeper understanding of the works and their meaning for the development of linguoculturology.
Keywords: Phraseological units; Linguoculturology; Inspector General